How common is gigantism in insular fossil shrews? Examining the 'Island Rule' in soricids (Mammalia: Soricomorpha) from Mediterranean Islands using new body mass estimation models. (12th May 2016) - Moncunill‐Solé, Blanca; Jordana, Xavier; Köhler, Meike
Abstract : The evolution of organismal body size in extant and extinct ecosystems of islands (Island Rule) is receiving much attention at present. Allometric models are a reliable way to predict the weight of extinct species, but are scarce or even absent for some groups of micromammals. To fill the gap, we carried out regression models with extant species of soricids ( N = 63) using measurements of teeth, cranium, and postcranial bones, and applied these to fossil insular species and their mainland ancestors. Almost all models are significant ( P < 0.05), except for those based on the width of occipital condyles. The femur can be considered the most reliable body‐mass predictor, producing estimations not far from those derived from teeth (excepting molar widths). Predictions of insular species (in grams) show that those belonging to the tribe Nectogalini [ Asoriculus burgioi Masini & Sarà, 1998, 27.54; Asoriculus similis (Hensel, 1855), 23.68; Nesiotites ponsi Reumer, 1979, 14.58; Nesiotites meloussae Pons‐Moyà & Moyà‐Solà, 1980, 24.83; Nesiotites hidalgo Bate, 1945, 26–30] had larger masses than Crocidura sp. [ Crocidura sicula esuae (Kotsakis, 1986), 9.50; Crocidura sicula sicula (Miller, 1901), 8.60; Crocidura zimmermanni Wettstein, 1953, 7–10]. Statistical comparisons with their ancestors revealed that certain species ( Nesiotites sp. from Mallorca and A. similis from Sardinia) may be considered giants, but not C. zimmermanni (from Crete). Body size is closely related to life history, which is highly influenced by the selective regimes of the environment. Thus, the lower isolation distance of Crete in comparison with Sardinia and Mallorca, suggesting more introductions of competitors and predators, and the presence of a flow with the mainland, may be the reason for the absence of a giant form of C. zimmermanni . However, some biological aspects of species (such as phylogeny or lifestyle) may also have an influential role.